Building Interpersonal Communication Skills in the Digital Age for Vocational Students in South Jakarta - Said Romadlan; Dini Wahdiyati; Hendri Prasetya; Ratih Novita Sari (Universitas Ibn Khaldun Bogor, 2023)
Interpersonal communication skills are a person's ability to establish personal relationships with others directly well. Amid the rampant development of communication and information technology today, interpersonal communication skills on the one hand are needed but on the other hand face challenges. In the digital age, people tend to prefer to communicate with others using social media rather than communicating face-to-face in person. People prefer using social media rather than socializing with others. As a result, interpersonal communication skills become undeveloped and inhibited. Among students, interpersonal communication skills are needed for self-development and soft skills, especially in building positive relationships with friends, teachers, family, and the social environment where they are. This Community Partnership Program offers solutions to build interpersonal communication skills among students of Al Falah Mampang Prapatan Vocational High School (SMK), South Jakarta. The results of this program show that students become more familiar with the concept of interpersonal communication skills, consider it important to have interpersonal communication skills, and are motivated to improve their interpersonal communication skills.